Ressurection Leadership Sebagai Model Kepemimpinan Bagi Perempuan Awam Merespons Panggilan Misi Allah - Lumintang, Merlin Brenda Angeline (IAKN TORAJA, 2025)
In Christianity, the accounts of women on a mission frequently lack adequate attention and discourse. Even though they had been involved in the calling to preach the gospel long before the church established itself in the organization it is today. This paper wants to explore the role of laywomen who are involved in the Christian mission movement but are often marginalized even though the mission movement attracts a lot of interest from the laity, especially women. Therefore, this paper focuses on the calling of laywomen as members of the Body of Christ in response to the mission of Dei. Using the metaphor of resurrection leadership, the results of this study show the crucial role of laywomen in mission history in response to the call of the Kingdom of God and its implications for Christian women in Indonesia.